1998
DOI: 10.1143/jjap.37.4144
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pt Bottom Electrodes using High-Temperature Sputtering for Ferroelectric Memories with SrBi2Ta2O9 (SBTO) Film

Abstract: Pt bottom electrodes for SrBi2Ta2O9 (SBTO) capacitors have been investigated for use in nonvolatile memories. A Pt thin film which is sputtered at a temperature of 300°C consists of enlarged columnar grains, while a film sputtered at room temperature consists of fibrous columnar grains. The formation mechanism of enlarged grains of the Pt film sputtered at 300°C is due to the fact that the film structure changes with substrate temperature based on the structure-zone model. The Pt bottom ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Intensity is logarithmically represented and we can observed that the two films are ͑111͒ oriented. 4 All the electron beam evaporated films exhibit tensile stress. 2͒.…”
Section: Experimental Procedures Of Metal Deposition and Annealingmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensity is logarithmically represented and we can observed that the two films are ͑111͒ oriented. 4 All the electron beam evaporated films exhibit tensile stress. 2͒.…”
Section: Experimental Procedures Of Metal Deposition and Annealingmentioning
confidence: 99%
“…Platinum is generally used because of its chemical stability in high temperature and its high temperature coefficient of resistance ͑TCR͒. [1][2][3][4][5]10 In this study, Pt/Ti bilayer deposition by ac sputtering and electron beam evaporation techniques is reported for the substrate temperature range from room temperature to 400°C. [6][7][8][9] Therefore, Pt/Ti must have a good adhesion onto a SiN x /Si substrate to prevent the peeling layer in the KOH solution and it must have a high TCR to increase the sensor sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum has been demonstrated as a versatile electrode material for ferroelectric materials in general [4][5][6][7][8][9]. The development of [111] texture for a perovskite as PZT on Pt(111) is expected.…”
Section: Introductionmentioning
confidence: 99%